An Exploratory Study of the Gaps and Barriers to Nutrition Education for Pregnant Women in Tamale, Ghana. (29th May 2020) - Ayande, Ruthfirst; Otoo, Gloria; Rousham, Emily; Hawley, Nicola; Carbone, Elena
Abstract: Objectives: Nutrition education (NE) remains a popular intervention to improve maternal health literacy (MHL), with the promise of behavior change and improved maternal and child health outcomes. However, there continue to be gaps and barriers that impede the delivery of NE to women, and/or affect maternal compliance to NE guidelines. This is the first phase of a larger project that examines the role of NE on MHL and pregnancy outcomes. Specifically, this phase aimed to identify the gaps in, and barriers to current NE delivered at hospitals to women in Tamale, Ghana. Methods: A series of focus group discussions were used to engage health providers and pregnant women. Field observations of the antenatal care (ANC) process and informal interviews with focal personnel were also employed. Data were thematized using recurrent themes from field notes and audio loggings. Results: Preliminary analysis of discussions with 33 health providers and 13 pregnant women identified 3 thematic areas describing gaps and challenges to successful delivery and implementation of NE: 1) Sociocultural: Women's adherence to NE advice was affected by constrained autonomy resulting from patriarchal norms including spousal control, polygamy, coercion, and financial abuse. Food insecurity resulting from low socioeconomic status and a lack of social safety nets also impacted maternal ability to access and comply with NE 2) Communication: Midwives were cited as the most common sources of information for women at ANC sessions, yet owing to dissatisfaction with the hospital set up, some mothers preferred and continued to seek health information from traditional birth attendants. Also, more emphasis was placed on anemia prevention at ANC visits compared to other salient topics like weight gain during pregnancy. 3) Administrative: Lack of professional language translation, health professional workload and inadequate health worker retraining also affected the quality of NE. Conclusions: Attention should be paid especially to the sociocultural factors plaguing vulnerable women in low-middle income settings like Tamale when designing NE interventions. The study investigators will continue to engage community members in exploring ways of incorporating these in the design of a NE intervention for pregnant women in the area. Funding Sources: N/A.